A sensitive label-free FRET probe for glutathione based on CdSe/ZnS quantum dots and MnO2 nanosheets. Issue 34 (17th August 2018) - Mi, Yueyao; Lei, Xiaoxue; Han, Heyou; Liang, Jiangong; Liu, Lingzhi
Abstract : A simple and sensitive label-free FRET probe for glutathione was constructed based on MnO2 nanosheet-modified CdSe/ZnS QDs@SiO2 nanobeads. Abstract : Glutathione (GSH) is an important antioxidant and plays crucial roles in basic biological functions. Thus far, it still remains a challenge to develop convenient and reliable ways to quantify and monitor the changes in bodily GSH levels. Herein, we have developed a simple, sensitive, and label-free fluorescence resonance energy transfer (FRET)-based probe for GSH with MnO2 nanosheets as an energy acceptor and silica coated CdSe/ZnS quantum dots (QDs) as the energy donor. The in situ synthesis of MnO2 nanosheets allowed the direct formation of QDs@SiO2 @MnO2 nanocomposites, and enabled the occurrence of FRET with the donor fluorescence to be quenched. Upon the addition of GSH, MnO2 nanosheets were decomposed, and QDs@SiO2 nanobeads were released with a remarkable recovery of the fluorescence intensity in a target-dependent manner. The established FRET probe showed excellent selectivity and sensitivity towards GSH. The feasibility of the probe for GSH detection in a complex matrix was further investigated by analyzing the GSH content in reduced glutathione tablets. The results indicated the capability of the probe to detect low concentrations of GSH and suggested the practicability of the probe for GSH determination in real samples.